2022
DOI: 10.3390/agriculture12070939
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Meat Quality, and Fecal Microbial Population in Limousin Bulls Supplemented with Hydrolyzable Tannins

Abstract: The objective of this study was to investigate the effects of supplementation of hydrolyzable tannins (HT) from sweet chestnut wood extract (Castanea sativa Mill.) to the diet of Limousin bulls on growth rate, carcass and meat quality traits, and fecal Clostridia strain levels in a 7-month feeding trial. Thirty-two bulls were randomly assigned to four treatment groups (CON (without addition of HT); TAN 1 (1 g HT kg−1 DM); TAN 2 (1.5 g HT kg−1 DM); and TAN 3 (1.5 g HT kg−1 DM with a nominally lower dose of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
6
2
Order By: Relevance
“…The average drip losses that were determined in the not weighed samples were 0.95% within 24 h, 1.30% within 48 h, and 1.38% within 72 h, whereas the weighed samples were 1.72% within 24 h, 2.70% within 48 h, and 3.62% within 72 h. Although there is considerable variability in WHC between animals, the following comparison with different species should give us deeper insight into the drip loss values that were obtained by different EZ-DripLoss methodologies. Greater average drip loss values of not weighed samples were found with beef [ 11 ] and deer meat [ 12 ] than the ones of the present technical report. Mergeduš et al [ 11 ] found that the average drip loss of meat from bulls that were fattened under commercial conditions was 1.40% within 48 h of storage period.…”
Section: Resultscontrasting
confidence: 48%
See 2 more Smart Citations
“…The average drip losses that were determined in the not weighed samples were 0.95% within 24 h, 1.30% within 48 h, and 1.38% within 72 h, whereas the weighed samples were 1.72% within 24 h, 2.70% within 48 h, and 3.62% within 72 h. Although there is considerable variability in WHC between animals, the following comparison with different species should give us deeper insight into the drip loss values that were obtained by different EZ-DripLoss methodologies. Greater average drip loss values of not weighed samples were found with beef [ 11 ] and deer meat [ 12 ] than the ones of the present technical report. Mergeduš et al [ 11 ] found that the average drip loss of meat from bulls that were fattened under commercial conditions was 1.40% within 48 h of storage period.…”
Section: Resultscontrasting
confidence: 48%
“…Greater average drip loss values of not weighed samples were found with beef [ 11 ] and deer meat [ 12 ] than the ones of the present technical report. Mergeduš et al [ 11 ] found that the average drip loss of meat from bulls that were fattened under commercial conditions was 1.40% within 48 h of storage period. Razmaitė et al [ 12 ] found that the average drip loss in meat from free-living red deer was 1.80% within 24 h, and from farmed red deer, it was 3.42% within 24 h.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Moreover, Taha et al [ 9 ] reported that adding chestnut tannin extract (CTE) to ryegrass silage reduces ammonia nitrogen (NH 3 -N) concentration in lamb rumen. In contrast, Mergeduš et al [ 10 ] discovered that supplementing CTE with a low-protein diet elevates growth performance and nutrition efficiency in bulls, without affecting slaughter performance or meat quality. The differences in these findings could result from the tannin dosage, source, type, animal species, health status, and feed composition [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this implementation serves as a preventive measure against boar taint by minimizing intestinal skatole production . The supplementation of HT in the diet of pigs, chickens, and bulls has been shown to accelerate their growth rate and improve gastrointestinal well-being, as evidenced by several studies. Additionally, it contributes to a reduction in enteric methane emissions in llamas and bulls …”
mentioning
confidence: 99%